Efficiency and effectiveness of human capital management information system in managing ghost workers fraud: A case of President’s Office, Public Service Management and Good Governance (POPSMGG)-Tanzania (Mzumbe University, 2024)
A dissertation submitted to the School of Public Administration and Management in partial fulfillment of the requirement for award of degree Master of Science in Human Resource Management (MSc-HRM) of Mzumbe University.